2012
DOI: 10.1111/jace.12137
|View full text |Cite
|
Sign up to set email alerts
|

Combined Hydrothermal Conversion and Vapor Transport Sintering of Ag‐Modified Calcium Phosphate Scaffolds

Abstract: Two processing methods were successfully combined to obtain Ag‐modified calcium phosphate scaffolds with antibacterial properties: (i) hydrothermal conversion of macroporous biogenic carbonates and (ii) vapor transport sintering. Hydrothermal conversion of two precursor materials, i.e., coral skeletons and sea urchin spines, resulted in the pseudomorphic replacement of highly porous calcium carbonates by calcium phosphate scaffolds. Vapor transport sintering of these scaffolds within a reactive AgCl atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…2 Moreover, the absorption peaks at 873, 1420, and 1460 cm À1 are also detected that indicate incorporation of CO 3 2À groups into HAp lattice structure through the B-type substitution. 13 The substitution maybe come from small amount of carbonate impurities in the raw materials. Figure 2 exhibits the SEM images of the HAp microspherical material.…”
Section: Resultsmentioning
confidence: 99%
“…2 Moreover, the absorption peaks at 873, 1420, and 1460 cm À1 are also detected that indicate incorporation of CO 3 2À groups into HAp lattice structure through the B-type substitution. 13 The substitution maybe come from small amount of carbonate impurities in the raw materials. Figure 2 exhibits the SEM images of the HAp microspherical material.…”
Section: Resultsmentioning
confidence: 99%
“…The zone of inhibition was measured as the maximum distance from the PAA-silver nanofiber scaffold in a number of directions at which an inhibition of bacterial growth was observed. This approach was already chosen in earlier studies [32,33]. These results showed that Silver NPs had multiple inhibitory actions for the interruption and blockage of activity against fungal and bacterial strains, which will minimize expenses required for disease control.…”
Section: Antimicrobial Activitymentioning
confidence: 94%
“…Pseudomorphic conversion of biocarbonate in contact with phosphate-bearing solutions takes place via interface coupled dissolution-recrystallization [16,22,33,34]. The conversion mechanism involves the dissolution of primary aragonite and the precipitation of secondary apatite [35][36][37][38][39][40].…”
Section: The Phase Conversion Mechanismmentioning
confidence: 99%
“…Consequently, the newly formed product layer commonly contains a certain amount of intrinsic intergranular porosity and does not seal completely the parent phase from further interaction with the solution [46,47]. In addition, the molar volume change associated with the aragonite-AP conversion is negative (−6%) [16,22,34]. As the external shape of the sample is preserved during conversion, porosity has to be generated to compensate the molar volume loss [35][36][37][38][39][40].…”
Section: The Conversion Of Geologic Aragonitementioning
confidence: 99%